Exploratory Study on the Relation between Urban Landscapes and Urban Corridors for Outdoor Thermal Comfort. (2016) - Anupriya, S.
Abstract: Urban Heat Island (UHI) is an increasing phenomenon experienced by most of the growing cites in India. Many researchers have proved that there is a substantial increase in surface temperature between urban and rural areas. The climatic conditions in the man-made urban environment is greatly influenced by roads, buildings and many other factors where the micro-climate of indoor environment can be controlled through various mechanisms whereas the thermal comfort of outdoor environment has very limited control. On the other hand the fundamental role of roads is to move people or goods from one place to another, thereby contributing to the economic development of any city. Roads are inevitable for city planning and are no longer perceived as mere transportation corridor; they can be seen as windows of surroundings and are places that offer high degree of social interaction between people. In the recent years owing to the growth of cities there is tremendous increase in road surface leading to increased UHI effect. This paper through a series of literature study tries to explore the possible relation between urban landscapes and roads towards comfortable outdoor environment. Landscaping is considered to be one of the effective means of passive cooling.